Against the Grain: Spanish Trade Policy in the Interwar Years - Betrán, Concepción; Huberman, Michael (The Journal of Economic History, 2022)
We study the effects of domestic conflict and external shocks on Spanish trade policy in the interwar period. Our account mobilizes a new granular dataset on exports and imports, and good-country level information on tariffs, trade agreements, and quotas. Into the Depression, the mainstay of policy was the tariff. The establishment of the Second Republic in 1931 was a turning point in policymaking. The new regime initiated bilateral trade negotiations. The Republic’s dilemma was to find countries willing to exchange market access. In a daunting international environment, the Spanish case offers a poignant reminder of the perils of going against the grain.